Osteocartilaginous metabolic markers change over a 3-week stage race in pro-cyclists. (October 2015) - Corsetti, Roberto; Perego, Silvia; Sansoni, Veronica; Xu, Jincheng; Barassi, Alessandra; Banfi, Giuseppe; Lombardi, Giovanni
Abstract Evidence suggests that endurance and even recreational cycling may stimulate bone resorption; however, little is known about cartilage response to endurance cycling exercise. We investigated effort-dependent changes in bone turnover and cartilage biomarkers in blood and urine samples from elite cyclists during a 3-week stage race. Whole blood and urine samples were collected the day before the start of the race, at mid and end-race for serum and urinary CTx-I, NTx-I, PINP, COMP (only in serum), and CTx-II analysis by enzyme-linked immunosorbent assay. The values were corrected for plasma volume or creatinine excretion, respectively, and correlated with power output (corrected for body weight) and net energy expenditure. Bone marker concentrations in both serum and urine were slightly but significantly decreased. Among the cartilage degradation markers, only CTx-II was decreased, while COMP remained unchanged. The changes in bone and cartilage turnover indexes were correlated with the indexes of physical effort and energy consumption. Strenuous physical effort, in the absence of mechanical loading, slows bone metabolism and only minimally affects cartilage turnover. Since changes in plasma and urine volume, which normally occur in exercising athletes, can mask these effects, biomarker concentrations need to be corrected for shifts in plasma volume and urinary creatinine for correct interpretation of the data.